2012
DOI: 10.1590/s1678-77572012000200020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of oral health in liver transplant candidates

Abstract: Liver transplantation has become a standard treatment for end-stage liver disease and the number of recipients has grown rapidly in the last few years. Dental care during pre-transplant workup is important to reduce potential sources of infection in the drug-induced immunosuppression phase of liver transplantation.Objectives The objectives of this study were to document the prevalence of oral abnormalities in patients on a liver transplant waiting list presenting to an urban dental school clinic, discuss the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 6 publications
1
35
0
16
Order By: Relevance
“…Although studies on the interaction between cirrhosis and periodontitis are still too limited to make assumptions regarding a potential cause-and-effect relationship, a higher incidence of periodontitis (ranging from 25%-68%) has been reported in cirrhotic patients compared with healthy controls (81,82), an observation that warrants further investigation. In a retrospective study, Aberg and colleagues showed an association between periodontal disease and progression of chronic liver disease, suggesting that dental disease could play a role in cirrhosis (83).…”
Section: Ahluwalia Et Al 2016 (56)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies on the interaction between cirrhosis and periodontitis are still too limited to make assumptions regarding a potential cause-and-effect relationship, a higher incidence of periodontitis (ranging from 25%-68%) has been reported in cirrhotic patients compared with healthy controls (81,82), an observation that warrants further investigation. In a retrospective study, Aberg and colleagues showed an association between periodontal disease and progression of chronic liver disease, suggesting that dental disease could play a role in cirrhosis (83).…”
Section: Ahluwalia Et Al 2016 (56)mentioning
confidence: 99%
“…In addition to periodontitis, cirrhotic patients exhibit numerous oral issues, such as petechiae (79), candidiasis (79), and xerostomia (79,80). Although studies on the interaction between cirrhosis and periodontitis are still too limited to make assumptions regarding a potential cause-and-effect relationship, a higher incidence of periodontitis (ranging from 25%-68%) has been reported in cirrhotic patients compared with healthy controls (81,82), an observation that warrants further investigation.…”
Section: Ahluwalia Et Al 2016 (56)mentioning
confidence: 99%
“…Three of them are subjected to basic periodontal treatment and 47 are subjected to multiple or simple extractions. Three surgical procedures result in postoperative complications (12).…”
Section: Medinformmentioning
confidence: 99%
“…Oral-source infections are a potential threat to transplant candidates because oral diseases tend to be more severe if left untreated in people who have received transplants (12).…”
Section: Oral Source Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation